Impact of Pharmaceutical Telecare on People with Asthma in a Public Pharmacy in the State of Rio Grande do Sul: A Feasibility Study - Nogueira Gossenheimer, Agnes; Rigo, Ana Paula; Alberti, Fernanda; Klimkowski Argoud, Vanessa; Velasques Paladini, Sheyla; Pedroso Tolio, Rodrigo; Turmina Fontanella, Andréia; Rodrigues Martins de Freitas, Gabriel; Schneiders, Roberto Eduardo (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2026)
Asthma is a chronic, heterogeneous, and inflammatory disease of the airways that requires specific care and adequate treatment to remain controlled. A feasibility study was conducted with patients from a public pharmacy in the state of Rio Grande do Sul, diagnosed with asthma. They were randomized into four groups: telephone intervention, video intervention, text message (SMS) intervention, and control group. The primary outcome was the change in asthma control assessed by the Asthma Control Test (ACT) at baseline and after three months. A significant increase in the mean ACT score was identified, rising from 15.0 to 17.6 points (p=0.026), but only in the video intervention group. The other groups did not show statistically significant changes. Finally, the use of technologies with audiovisual resources proved effective in improving the use of inhalation devices, resulting in better asthma control.